Classification of Translation Surfaces in R3 with Constant Sectional Curvature for the Canonical snm-Connection - Aydin, Muhittin Evren; Lopez, Rafael; Mihai, Adela (Springernature, 2025)
In this paper, we study translation surfaces in the Euclidean space endowed with a canonical semi-symmetric non-metric connection. We completely classify the translation surfaces of constant sectional curvature with respect to this connection, proving that they are generalized cylinders. This consequence is the same as in the case of the Levi-Civita connection, but, in this new setting, there are also generalized cylinders whose sectional curvature can be constant or non-constant, in contrast to the Levi-Civita connection, where the Gaussian curvature is zero.
Keywords: Translation surface; Sectional curvature; Semi-symmetric connection; Non-metric connection